Surgical removal of brain stem cavernous malformations: surgical indications, technical considerations, and results. Issue 3 (1st March 2002) - Sandalcioglu, I E; Wiedemayer, H; Secer, S; Asgari, S; Stolke, D
Abstract : Objectives: This study was undertaken to review the indications for surgical treatment of brain stem cavernomas and to develop strategies to minimise the complications of surgery. Patients and results: Twelve patients underwent surgical resection of a brain stem cavernoma due to symptoms caused by one or more haemorrhages. Age ranged from 18 to 47 years (mean 29.2 years). Long term follow up (mean 3.7 years) included a complete neurological examination and annual MRI studies. The annual haemorrhage rate was 6.8 %/patient/year and a rate of 1.9 rehaemorrhages/patient/year was found. Surgery was performed under microsurgical conditions with endoscopic assistance, use of neuronavigation, and neurophysiological monitoring. Navigation proved to be reliable when applied in an early stage of operative procedure with minimal brain retraction. Endoscopy was a useful tool in some cases to confirm complete resection of the lesion and to ascertain haemostasis. Ten patients had a new neurological deficit in the early postoperative period, nine of these were transient. At the last follow up the neurological state was improved in five patients, unchanged in six, and worse in one compared with the preoperative conditions. The preoperative average Rankin score was 2.2 points and had improved at the last follow up by 0.6 points to 1.6 points. Conclusions: Symptomatic brain stem cavernomas should be considered for surgical treatment after the first bleeding. Careful selection of the optimal operative approach and a meticulous microsurgical technique are mandatory. The additional use of modern tools such as neuronavigation, endoscopic assistance, and monitoring can contribute to the safety of the procedure.